FINTECH INNOVATIONS AND THE TRANSFORMATION OF TRADITIONAL BANKS - Shokhzod Khujamurotov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: In this article, the impact of fintech innovations on the traditional banking sector is analyzed. Fintech products, such as mobile payments, neobanks, and solutions based on artificial intelligence (AI), are posing new challenges to banks’ business models. The article examines types of fintech and their impact on banking services, as well as the adaptation strategies of traditional banks, which include digital transformation, investment in innovations, and open banking. Furthermore, the development of the fintech ecosystem in Uzbekistan and changes in the local banking sector are analyzed. In conclusion, findings on future trends and the role of cooperation between banks and fintech in shaping the future of financial services are presented.